Estado trófico de uma lagoa costeira : lagoa Juara, Serra–ES - Venturini, Jéssica Cruz (2015)
Coastal lagoons are very affected by unplanned land development in the coastal zone. Therefore, these ecosystems are subjected to several environmental impacts, such as eutrophication process, which is the main cause of water quality decrease in these ecosystems. The Juara lagoon (2.71 km²) is located in the city of Serra (ES) and is widely used for recreation, fish farming and fisheries. However, the lake has been subject to numerous impacts such as sewage discharge, as well as deforestation of its margins and surroundings. Therefore, understanding of the aquatic ecosystem dynamics becomes essential for the preservation and maintenance of the functionality of the water body. This study aimed to evaluate the variability of lagoon trophic conditions by means of limnological indicators (physicochemical parameters, nutrients, TN:TP ratios and chlorophyll a and lake morphometry, and the trophic state indexes - TSIs proposed by Toledo-Jr et al. (1984) Burns et al. (2000) and Lamparelli (2004). Water samples were taken at five sampling stations distributed along the longitudinal axis of the lake, in 4 consecutive weeks in the rainy season and 4 consecutive weeks in the dry season in the year of 2014. Local factors such as land use, were crucial on the limnological characteristics of the lagoon, which was observed spatial variation associated with two distinct compartments: the upstream portion, influenced by rural regions, presenting higher TN:TP (10,7 – 39,2) ratios and mesotrophic conditions; and the downstream portion, influenced by sewage, with the lowest TN:TP (10,0 – 27,2) ratios and eutrophic conditions. The Juara lagoon has morphometric characteristics (i.e. low depht and higher fetch to winds from SE-NW) associated to eutrophication processes. Temporally, turbidity, conductivity, pH and N-NO3 variables showed a significant difference between samplings. The TSI proposed by Burns et al. (2000) and Lamparelli (2004) showed similar results regarding the classification of the trophic state of the lake and were more appropriate than the TSI proposed by Toledo-Jr et al. (1984), once this last one tends to underestimate the trophic condition of the lagoon.